(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Service organizations prioritize customer satisfaction by constantly offering new services, programs, equipment, and facilities to meet their needs. School management should assess its collection to identify strengths and weaknesses to maintain a well-stocked library. This will help them make necessary enhancements to sustain and upgrade the library’s quality and suitability. This study encourages school administrators to develop a feasible library development programme. This survey research focuses on the expectations and perceptions of Bestlink College of the Philippines’ students regarding library resources, staff services, access to information, and general services. The survey questionnaire was given to 50 students from 1st to 4th-year levels and analyzed using weighted means. Based on the analysis, most respondents were highly or poorly satisfied with the services provided by the Bestlink College of the Philippines Library. The researchers used this paper to understand the students’ expression towards the BCP library and provide recommendations to strengthen its resources and services. The study aims to assess the library resources available to students at Bestlink College of the Philippines. The study was conducted during the 2021-2022 academic year and only includes students who use the library. The respondents included college students from various Bestlink College of the Philippines courses.